Challenges of the Science EduXplore Program and Alternative Solutions in Biology Learning through Outdoor Learning and Digital Transformation - Miftahul Jannah; Syafira Defni; Juju Juwita; Bambang Supriatno; Sariwulan Diana (BIO-EDU: Jurnal Pendidikan Biologi, 2026)
This study aims to analyze the implementation challenges of the Science EduXplore 2025 program and identify alternative solutions for its future development. The program represents an innovative biology learning model that integrates outdoor learning and digital transformation approaches. This research employed a descriptive quantitative method with a cross-sectional design. Data were collected through questionnaires completed by 30 junior high school participants and analyzed using descriptive statistics. The results indicate that participants generally responded positively to the program, particularly in terms of engagement, meaningfulness, and facilities. However, several challenges were identified, including limited exploration time, difficulties in using scientific tools, and the perceived relevance of the material. Based on these findings, alternative solutions were proposed, such as utilizing QR codes, mobile-based scientific sensor applications, and developing interactive e-modules. In addition, a differentiated approach based on educational levels (junior and senior high school) was implemented to align the complexity of the material. These findings suggest that integrating outdoor learning with digitalization holds significant potential to foster active, contextual, and reflective biology learning, and can serve as a foundation for sustainable educational program development.